PENGGUNAAN CURRENT RATIO, DEBT TO EQUITY RATIO, DAN RETURN ON EQUITY, UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Eefek Indonesia Periode Tahun 2010-2013) (Students' Journal of Accounting and Banking, 2015)
This research is a study that tested the effect of the ratio of CR, DER, and ROE for Financial Distress. Analysts financial ratio is one tool to estimate or determine the company's financial condition. If the performance is increased by the value of the company will be higher In this study, researchers used a purposive sampling and obtained a sample of 252 sample companies listed on the Stock Exchange. Data company then tested using logit regression to explain the relationship between these variables. The results of this study indicate that CR not significant negative effect on financial distress, while striving DER variable is positive and significant to the financial distress, and ROE significant positive effect on the financial distress.Keywords: CR, DER, ROE and Financial Distress